Ixabepilone: Overview of Effectiveness, Safety, and Tolerability in Metastatic Breast Cancer - Ibrahim, Nuhad K. (Frontiers in Oncology, 2021)
Treatment algorithms for metastatic breast cancer describe sequential treatment with chemotherapy and, if appropriate, targeted therapy for as long as the patient receives benefit. The epothilone ixabepilone is a microtubule stabilizer approved as a monotherapy and in combination with capecitabine for the treatment of metastatic breast cancer in patients with demonstrated resistance to anthracyclines and taxanes. While chemotherapy and endocrine therapy form the backbone of treatment for metastatic breast cancer, the epothilone drug class has distinguished itself for efficacy and safety among patients with disease progression during treatment with chemotherapy. In phase III trials, ixabepilone has extended progression-free survival and increased overall response rates, with a manageable toxicity profile. Recent analyses of subpopulations within large pooled datasets have characterized the clinical benefit for progression-free survival and overall survival for ixabepilone in special populations, such as patients with triple-negative breast cancer or those who relapsed within 12 months of prior treatment. Additional investigation settings for ixabepilone therapy discussed here include adjuvant therapy, weekly dosing schedules, and ixabepilone in new combinations of treatment. As with other microtubule stabilizers, ixabepilone treatment can lead to peripheral neuropathy, but evidence-based management strategies may reverse these symptoms. Dose reductions did not appear to have an impact on the efficacy of ixabepilone plus capecitabine. Incorporation of ixabepilone into individualized treatment plans can extend progression-free survival in a patient population that continues to represent an unmet need.